Cu-P-Se nanoparticles: understanding the reaction pathways for the colloidal synthesis of energy conversion and storage materials - Neisius, Nathan A., author; Prieto, Amy L., advisor; Finke, Richard, committee member; Herrera-Alonso, Margarita, committee member; Paton, Robert, committee member (Colorado State University. Libraries, 2024)
Nanotechnology has garnered considerable interest over the last 40 years, owing to the unique, desirable properties that can be targeted through established synthetic methods for tuning the size of materials at the nanoscale. As no one single material has properties suitable for a wide range of applications, property driven synthesis has been at the forefront of the nanoparticle (NP) field. Particularly, colloidal NP syntheses provide a large synthetic landscape to explore as a result of the vast synthetic tunability to target specific parameters such as, particle size, morphology, composition, and defects. Although significant efforts have been made toward deciphering the transformation processes of unary and binary NPs, traditionally the colloidal NP field has been driven by a top-down approach, driven by trial-and-error methods, limiting the design of desired, complex materials. Thus, to further progress nanoparticle technology, understanding the underlying transformation processes occurring throughout the formation of colloidal nanoparticles is essential to develop novel materials as well as control the structure/property relationships. The copious amounts of both organic and inorganic interactions, as well as the complexity of capturing the transformation from molecular to the solid-state regime, complicates the reaction landscape for more complex, ternary phases. The purpose of the work included and explained in this dissertation is to develop stoichiometric syntheses for both Cu-P-Se ternary phases, Cu3PSe4 and Cu7PSe6, and to then understand the reaction pathways for an improved retrosynthetic analysis and enable translation of the synthetic knowledge to other systems. Cu-P-Se ternary chalcogenide NPs are of particular interest, owing to the synthetic complexity of navigating a rich phase space with thermodynamically stable binary phases close in energy to the desired ternary phases, as well as applicable structural properties for thermoelectrics, photovoltaics, and battery applications. Therefore, to contribute to the progression of the nanoparticle field the general objectives of this study are, (1) analyzing the transformation of commonly employed precursors and solvents (2) capture the influence of precursor reactivity on ternary phase formation, and (3) perform careful characterization of speciation and final nanoparticles, all of which to establish a full scope of Cu-P-Se nanoparticle formation and the impact of individual synthetic parameters on chalcogenide-based precursors. In Chapter 1, the relevant literature for the following chapters is reported and reviewed to provide the essential background information. This chapter is divided into 6 subsections; (1) Need for renewable energy and how nanoparticles provide solutions, (2) State of nanoparticle synthesis field, current limitations, and progress towards developing a better understanding of nanoparticle reaction pathways, (3) Motivation for exploring the Cu-P-Se phase space, (4) Se reactivity in NP syntheses, (5) Cu3P – the required precursor for Cu-P-Se formation, (6) Dissertation overview, publications, and presentations. The first colloidal NP synthesis report on Cu3PSe4 was developed by a previous group member, Dr. Jennifer Lee, which demonstrated that the phase purity of Cu3PSe4 requires the use of Cu3P NPs and selenium powder (Se) in ODE as precursors. Alternate reaction precursors, and therefore pathways, were disproven throughout this study, leading to the working hypothesis that the interactions of Se and ODE were a necessary step to form active species that then react with Cu3P NPs. Although frequently employed in NP research, and heavily characterized, the implications of the Se/ODE solution on Cu3PSe4 phase formation are still misunderstood. Therefore, the studies presented in Chapter 2 are aimed at probing the Cu3PSe4 reaction landscape and the findings are separated into (1) ex situ reactions that are characterized with molecular and solid-state characterization techniques to determine the implications of the solution dynamics on Cu-P-Se NP phase formation, and (2) how different Se/ODE speciation can be isolated and subsequently favor the alternate, metastable Cu-P-Se phase, Cu7PSe6. A persistent limitation to the previous study is that ODE contaminates the final products, making the findings and analysis of Se/ODE rather difficult to interpret, thus requiring a simplified, cleaner reaction to produce phase pure Cu3PSe4. For that reason, Chapter 3 shifts the direction of the Cu3PSe4 synthesis towards a more stoichiometric, atom-economical reaction by eliminating ODE as the solvent. Rather, a long-chain, aliphatic solvent, octadecane (ODA) is employed that proves to be an operationally inert solvent under the standard synthetic conditions and produces cleaner, phase pure Cu3PSe4 NPs as determined by powder X-ray diffraction (PXRD) and transmission electron microscopy (TEM). If ODA was reacting with Se0 powder, the most favorable pathway, commonly cited in literature, is the formation of H2Se and oxidized ODA (alkene). Hence, molecular characterization techniques, nuclear magnetic resonance (NMR, 1H and 13C) and fast-Fourier infrared spectroscopy (FT-IR), were utilized to demonstrate the absence of oxidized ODA species, which is consistent with Se0 preferentially reacting with Cu3P, promoting a more direct reaction pathway. Eliminating the presence of alternate, competing reaction pathways in the ODE synthesis and establishing a near-stoichiometric reaction, allows us to capture the underlying transformation process of Cu3P to Cu3PSe4. From these systematic improvements, we hypothesize that Se0 powder is dispersed in ODA, which promotes a formal eight-electron transfer between Cu3P and 4 Se0. Extracting the synthetic information from the previous chapters to target the metastable Cu-P-Se phase, Cu7PSe6, provides the framework for Chapter 4. Previous methods to isolate Cu7PSe6 are based on traditional, solid-state techniques, where the elemental precursors are ground and subsequently heated to high temperatures (>1000K). Although a colloidal or solution-based synthesis has yet to produce phase-pure Cu7PSe6 particles, attempts explained in Chapter 2 provide a basis on the phase space complexity, where the products consisted of Cu7PSe6 but with thermodynamic byproducts, Cu-Se phases and Cu3PSe4 present. Therefore, an alternate Se precursor, diphenyl diselenide (Ph2Se2), is employed to form the metastable phase, which effectively avoids Cu3PSe4 formation. Importantly, an alternate route to form Cu3PSe4 is with analogous dialkyl diselenide precursor, dibenzyl diselenide, where a key finding is the presence of amorphous phosphorus (P) on Cu1-xSe binaries at low temperatures, which then efficiently reincorporates once the desired 300 ˚C reaction temperature is reached. Thus, in Chapter 4 we investigate why Cu7PSe6 is favored with Ph2Se2 as a precursor, which is predicated on the formation of byproduct species that effectively "trap" P. A proof of concept is explored to further demonstrate the dynamics of P in solution, where the Cu-P-Se phase space can be controllably toggled across by injecting P(5+) species. A drawback for the Cu-P-Se syntheses is the lack of compositional understanding of the pre-synthesized Cu3P NPs, thus further complicating the reaction stoichiometries. Chapter 5 first investigates the previously published synthesis by Liu et al., by thoroughly characterizing the final Cu3P nanoparticles under identical reaction conditions and exploring alternate reaction stoichiometries to reduce the presence of residue precursors. From such, it is determined that the particles substantially deviate from the stoichiometric Cu3P composition, with a Cu:P ratio around 1.5:1.0. Particular focus is also placed on monitoring the degradation of a green phosphorous source, triphenyl phosphite, P(OPh)3. Although triphenyl phosphite (TPOP) has been previously used for transition metal phosphide systems, a lack of systematic investigations leads to questions on the reduction of TPOP en route to forming Cu3P, a formal P(3+) to P(3-) event. Additionally, limited characterization of the final organic byproducts in the original synthesis, begs to question what, if any, byproducts could be contaminating the Cu3P NPs. Therefore, we develop and probe stoichiometric syntheses that isolate phase pure Cu3P NPs to avoid the original 30-fold excess of P. The transformation of hexadecylamine (reductant and ligand) and TPOP were characterized with 1H and 31P NMR to evaluate the role of each en route to forming Cu3P. As this is project is still developing, the necessary future directions are given to systematically approach this problem, with an emphasis on first-step experiments and essential characterization methods to completely grasp the decomposition mechanism of TPOP. Ultimately, this has implications when systematically applying TPOP to alternate transitional metal phosphide NP syntheses, as well as developing more precise Cu-P-Se syntheses. Finally, the work presented herein is summarized in Chapter 6 along with an outlook on the project as a whole. Specifically, future directions and preliminary insight into the underlying reaction pathways and mechanism of Cu3PSe4 formation are explored. Additionally, we explore preliminary data on an analogous material Ag-P-Se, which was plagued for years by the lack of a reproducible Ag-P precursor synthesis that limited our ability to extract the synthetic intuition from the Cu-P-Se system. However, recent literature findings on a potential Ag3P precursor provides promise on synthesizing Ag-P-Se phases in the future, which is critically analyzed to ensure that any bottlenecks in future syntheses are limited. Ultimately, the work provided in the following chapters is aimed at making strides to developing a more in depth understanding of precursor interactions between transition metals and main group elements, as well as properly monitoring such reactions to extract synthetic information to analogous systems. With the knowledge gained on the presented studies, we aspire to contribute to the NP field in order to continually improve NP synthesis and therefore nanomaterials. Finally, this work is supported by NSF Macromolecular, Supramolecular, and Nanochemistry (MSN #2109141).
Keywords: nanoparticle synthesis; nanomaterials